2004
DOI: 10.1097/00004872-200412000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of central and peripheral body fat distribution on sympathetic and baroreflex function in obese normotensives

Abstract: These data suggest that CO is characterized by a sympathetic activation greater for magnitude than that detectable in PO. This appears not to be related to gender or to baroreflex mechanisms but rather to metabolic factors, i.e. to the greater insulin resistance characterizing CO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
213
1
12

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 292 publications
(241 citation statements)
references
References 30 publications
13
213
1
12
Order By: Relevance
“…This is shown in Fig. 3, which displays the results of a recent microneurographic study in which the muscle sympathetic neural drive was assessed in abdominal as well as in peripheral obesity (20). The results clearly indicate that the degree of sympathetic activation (and the magnitude of the insulin resistance state) is much greater in patients with visceral body fat deposits than in those with peripheral distribution of the adipose tissue.…”
Section: Sympathetic Function In Hypertension and In Obesitymentioning
confidence: 75%
See 1 more Smart Citation
“…This is shown in Fig. 3, which displays the results of a recent microneurographic study in which the muscle sympathetic neural drive was assessed in abdominal as well as in peripheral obesity (20). The results clearly indicate that the degree of sympathetic activation (and the magnitude of the insulin resistance state) is much greater in patients with visceral body fat deposits than in those with peripheral distribution of the adipose tissue.…”
Section: Sympathetic Function In Hypertension and In Obesitymentioning
confidence: 75%
“…This is based on the evidence that 1) cardiovascular as well as metabolic function are modulated by sympathetic mechanisms and 2) several of the pathologic states clustering in the metabolic syndrome already display an increased adrenergic drive (2,3,10,(18)(19)(20). This is also based on the finding that when obesity and hypertension are concomitantly present in the same patient, the degree of sympathetic activation is much greater than in patients with either condition singly (24).…”
Section: Sympathetic Overdrive In the Metabolic Syndromementioning
confidence: 99%
“…It has been known for over two decades that insulin stimulates sympathetic activity [4] and, more recently, that this stimulation occurs at levels of insulin that are well within the physiological range [5]. For the last 15 years it has been known that obese humans have increased sympathetic activity [6], and Grassi and colleagues recently demonstrated that sympathetic activation is greater in subjects with the central, as opposed to the peripheral, form of obesity [7]. It is a reasonable inference, therefore, that insulin stimulates the sympathetic nervous system in obese individuals and that insulin-mediated sympathetic stimulation exerts a pro-hypertensive effect in this group.…”
mentioning
confidence: 99%
“…The differences between these two studies might be attributed to the greater number of men with visceral obesity in Grassi's study [Jones et al, 1996;Grassi et al, 2005] because central obesity increases mSNA more markedly than peripheral obesity Grassi et al, 2004].…”
Section: Sympathetic Activation Associated With Obesitymentioning
confidence: 93%
“…Third, central obesity and obesity-related hypertension attenuate the inhibitory action of baroreflex on sympathetic outflow [Grassi et al, 2000;Beske et al, 2002;Grassi et al, 2004]. Conversely, weight loss improves baroreflex function [Alvarez et al, 2005].…”
Section: Sympathetic Activation Associated With Obesitymentioning
confidence: 99%